Exploring the utility of dynamic motor control to assess recovery following pediatric traumatic brain injury: A pilot study - Nanette Aldahondo; Andrew J. Ries; Amy Schulz; Michael H. Schwartz (PLoS ONE, 2026)
Pediatric traumatic brain injury often leads to long-term disability. Unfortunately, while currently used standard clinical measures can effectively capture secondary functional impairments, they do not measure neurologic impairment directly. Therefore, the objective of this study was to evaluate the feasibility of walking dynamic motor control (walk-DMC) assessments to more directly measure neurological impairment and recovery for individuals post-traumatic brain injury. To accomplish this, we assessed the trajectory of walk-DMC (a single summary measure that reflects the overall complexity of muscle activation patterns during walking) and standard clinical measures of balance, mobility, and function in a small cohort of individuals post-traumatic brain injury at different time points post-injury (during acute rehabilitation, short- and long-term follow-up). At enrollment all participants demonstrated substantial neurological impairment. All clinical measures showed an initial deficit followed by recovery, with most returning to nondisabled ranges over the study period for all participants. In contrast, walk-DMC scores demonstrated an initial acute deficit and did not reach nondisabled ranges for two of the participants, indicating persistent neurologic impairment. The findings of our pilot study show the promise of Walk-DMC’s ability in identifying subtle ongoing neurologic impairment compared to traditionally used clinical assessments of balance, mobility, and function. Further work in a larger cohort of participants with traumatic brain injury will improve understanding of how walking dynamic motor control changes with injury severity and where such a measure can serve as a leading indicator of neurologic and functional recovery.